If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + x + -6 = 7 + -4 Reorder the terms: 3 + -6 + x + x = 7 + -4 Combine like terms: 3 + -6 = -3 -3 + x + x = 7 + -4 Combine like terms: x + x = 2x -3 + 2x = 7 + -4 Combine like terms: 7 + -4 = 3 -3 + 2x = 3 Solving -3 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 3 + 3 2x = 3 + 3 Combine like terms: 3 + 3 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 2/3*7x-9/10 | | -3k-8+7=-21 | | 10y+6=5y+21 | | 1/3xd=1/10 | | x+9-19+x=64-x-1 | | 9=17+3x | | 100y+5=75y+25 | | 8(4-y)+10y=6y | | 19x+(-5)=-26+12x | | M=3m+10 | | 5x+10x+17x+4x=360 | | 16x^3-20x^2+12x-15= | | 4(2+2r)-2(-r+1)=6r+-2r | | M-8=3m+2 | | 21=6(5r-2) | | 3x+3-9=3+7-4 | | 2x+3(x-8)=9-5x | | 8x-25=6x-5 | | 100/15 | | -7x+23=-21-31x | | 36k^3=35 | | 2x+2+6x+1=5x-21 | | -0.7x+2.3=-2.1-3.1x | | -3x=-64+1 | | (5k^2-4k-1/5k^2-12k-7) | | 4y+12=-4(2y+5) | | 120x^2-116x-28= | | -x/5=75 | | B+3=2b-q | | 3xp=2qr-10qp | | 3log(2)x=3log(2)3 | | -7w+2=5w-10 |